The Feud of Nemo Plus Iuris Ad Alium Transferre Potest Quam Ipse Habet and Nemo Dat Quad Non Habet (Nemo Dat Rule) Legal Principles Against The Legal Principle of Good Faith (Bona Fides) in Indonesian Courts - Yonatan, Yonatan; Agustina, Rosa (Indonesia Law Review, 2022)
Abstract A dispute over ownership of land rights between the real Original Owner and a Good Faith Purchaser can be assumed as a dispute over legal principles in the field of civil law, namely: the legal principle of Nemo Plus Iuris Ad Alium Transferre Potest Quam Ipse Habet, and the legal principle of Nemo Dat Quad Non Habet (Nemo Dat Rule) against the legal principle of good faith (bona fides). The legal principle of Nemo Plus Iuris Ad Alium Transferre Potest Quam Ipse Habet and the legal principle of Nemo Dat Quad Non Habet (Nemo Dat Rule) are legal principles that defend the interests of the Original Owner when suing a Good Faith Purchaser. On the other hand, the legal principle of good faith (bona fides) defends and protects Good Faith Purchaser from claims by the real Original Owner. This article discusses and presents 3 (three) main points, all of which are: firstly, analyzing the legal principle of Nemo Plus Iuris Ad Alium Transferre Potest Quam Ipse Habet, the legal principle of Nemo Dat Quad Non Habet (Nemo Dat Rule), and the legal principle of good faith (Bona Fides); secondly, analyzing the types of claims and determine the most appropriate type of claim for disputes over ownership of immovable property between the real Original Owner and the Good Faith Purchaser; lastly, doing an analysis on how to conceptualize good faith. The research method used in this article is normative juridical research with statutory, case and conceptual approaches. There are several research findings, namely; first, there has been a shift in the paradigm of judges who are initially more inclined to defend the Good Faith Purchaser than the real Original Owner, to become more neutral in placing the legal principle of Nemo Plus Iuris Ad Alium Transferre Potest Quam Ipse Habet and the legal principle of Nemo Dat Quad Non Habet (Nemo Dat Rule) with the principle of good faith (Bona Fides); second, the application of procedural law practices regarding types of claims for ownership disputes between the real Original Owner and the Good Faith Purchaser, which is commonly used in practice, turns out to be inappropriate; finally, conceptualizing good faith is done by conceptualizing bad faith based on the permanent jurisprudence of court decisions. Keywords: nemo plus iuris, nemo dat, bona fides, good faith.